2020
DOI: 10.1186/s41938-020-00310-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bacillus and Trichoderma species in the management of the bacterial wilt of tomato (Lycopersicum esculentum) in the field

Abstract: Background Bacterial wilt caused by Ralstonia solanacearum is one of the most devastating diseases in tomato cultivation. This study aimed to evaluate the effect of Bacillus and Trichoderma isolates to manage the bacterial wilt disease. Main body of the abstract Field experiments were conducted in a randomized complete block design at Mwea and Kabete sites in Kenya. The treatments included 3 Trichoderma; 2 Bacillus isolates; a mixture of T1, T2, and T4; chemical standard; and distilled water as control. Tric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…Eighteen out of twenty-five isolates reduced wilting significantly on both varieties L390 (highly susceptible) and L180 (moderated resistant) compared to the negative control (Table 1). Previous studies have reported different fungal and bacterial isolates that were able to control bacterial wilt in tomato [16][17][18]. Wilting percent on L390 was higher than on the moderately resistant cultivar L180 treated with biocontrol.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Eighteen out of twenty-five isolates reduced wilting significantly on both varieties L390 (highly susceptible) and L180 (moderated resistant) compared to the negative control (Table 1). Previous studies have reported different fungal and bacterial isolates that were able to control bacterial wilt in tomato [16][17][18]. Wilting percent on L390 was higher than on the moderately resistant cultivar L180 treated with biocontrol.…”
Section: Resultsmentioning
confidence: 90%
“…Further, DNA sequencing identified distinct species: isolate 52-86 was a Talaromyces sp., 26-81 was a Trichoderma sp., 106-85 was a Bacillus sp., and 106-86 was a Variovorax sp. Distinct species of BCA might differ in the mechanism of action yielding differences in biocontrol efficacy [6], and genetic variation within the same species of BCA that might cause variability in control efficacy [16,21]. Higher W% was observed in some biocontrol treatments compared to the negative control suggesting an interaction between the biocontrol pathogen and the plant [6,22].…”
Section: Resultsmentioning
confidence: 99%
“…Cow manure was used as a carrier for Bacillus subtilis and Trichoderma isolates. Following guidelines by [ 24 ] with minor modification, 50 mL of colonized cow manure solution containing 1.5 × 10 13 CFU. g −1 of B. subtilis and 4.71 × 10 8 CFU.…”
Section: Methodsmentioning
confidence: 99%
“…First, approximately 75 ml of sterilized water was added to 4.5 kg of dry soil to wet the soil. A total of 450 ml of R. solanacearum cell suspension (approximately 8×10 8 cfu ml -1 ) was sprayed onto the soil and mixed (final cell concentration of 8×10 7 cfu g -1 soil) (Kariuki et al 2020), and then 300 g of soil amended with R. solanacearum was collected in sterile plates (diameter: 20 cm) by sterile weighing spoons for each treatment. K-Phite or strain F8 was applied to each treatment according to the treatment design.…”
Section: The Effect Of the Combined Application Of B Amyloliquefacien...mentioning
confidence: 99%